Law Evasion through Choice of Law Clauses in International Business Contracts: An Indonesian Study - Meher, Montayana; Kurniati, Agata (Universitas Muhammadiyah Purwokerto, 2026)
This article examines the problem of law evasion through choice-of-law and forum-selection clauses in international business contracts in Indonesia, focusing on how the absence of a codified private international law (PIL) framework generates inconsistent judicial responses. The central research problem concerns the uncertainty surrounding the limits of party autonomy vis-à-vis mandatory rules and public policy, particularly in cross-border transactions intensified by regional economic integration and global supply chains. Using doctrinal analysis, the study synthesizes four leading cases: Nine AM Ltd v. PT BKPL, Asuransi Harta Aman Pratama Tbk v. PT Pelayaran Manalagi, PT Rainbow Indah Karpet v. PT TNT Skypak, and Alexander William Ford v. Man Lee Ford Cheung. This study finds that courts tend to enforce foreign governing-law and forum clauses in highly internationalized and standardized sectors such as marine insurance and logistics, while prioritizing mandatory rules and public policy, most notably the Indonesian-language requirement under Law No. 24 of 2009, when disputes implicate domestically sensitive interests. This selective approach produces vertical and horizontal inconsistencies across court levels and panels, undermining legal certainty, encouraging forum shopping, and creating risks of both under- and over-enforcement of protective norms. To narrow the scope for law evasion while aligning Indonesia with comparative private international law standards and regional commercial expectations, this article recommends: (1) codifying party autonomy as the default governing principle for international commercial contracts; (2) adopting a proportionality-based test to assess the application of overriding mandatory rules and public policy exceptions; (3) clarifying the normative scope, legal consequences, and available remedies under Law No. 24 of 2009 in the context of private contracts; and (4) developing judicial guidance to ensure a consistent assessment of foreign nexus, sectoral sensitivity, and the protection of weaker parties.